Keanekaragaman Jenis dan Status Konservasi Ikan Pari (Batoidea) di Pelabuhan Pendaratan Ikan (PPI) Kedonganan - Lamonde Tarigan, Alexi Jaka; Giri Putra, I Nyoman; Widiastuti, Widiastuti (Journal of Marine Research and Technology, 2026)
This study aims to assess the species diversity and conservation status of rays (Batoidea) landed at the Kedonganan Fish Landing Port (PPI Kedonganan), Bali. Data were collected using a survey method with a descriptive quantitative approach conducted during March–April 2025 through 10 observation periods with intervals of 3–4 days. Species identification was based on morphological characteristics, while diversity analysis was performed using the Shannon–Wiener diversity index (H’), evenness index (E), and dominance index (C). The results showed that four ray species belonging to two families were recorded, namely Neotrygon australiae, Taeniura lymma, Maculabatis gerrardi, and Gymnura zonura, with a total of 151 individuals. Neotrygon australiae exhibited the highest relative abundance (38.41%), followed by Maculabatis gerrardi (27.81%), Taeniura lymma (23.84%), and Gymnura zonura (9.93%). The Shannon–Wiener diversity index value of 1.29 indicates a moderate level of diversity, with high evenness (E = 0.93) and low dominance (C = 0.291). Based on the IUCN Red List 2025, Taeniura lymma is classified as Least Concern (LC), Neotrygon australiae as Near Threatened (NT), while Maculabatis gerrardi and Gymnura zonura are categorized as Endangered (EN). These findings indicate that PPI Kedonganan is an important landing site for rays but also poses potential pressure on threatened species, highlighting the need for conservation-based fisheries management to ensure sustainability.